PTH-198 Preoperative parenteral nutrition in crohn's disease patients requiring abdominal surgery. (22nd June 2015) - Le Couteur, J; Patel, K; O'Sullivan, S; Ferreira, C; Williams, AB; Darakhshan, AA; Irving, PM; Sanderson, JD; McCarthy, M; Dunn, J
Abstract : Introduction: The benefits of parenteral nutrition (PN) in Crohn's Disease (CD) prior to abdominal surgery remains debatable, with two recent studies suggesting preoperative PN given to patients with moderate to severe CD minimises the risk of early postoperative complications. Method: Retrospective cohort study of consecutive CD patients who received PN prior to abdominal surgery, from January 2013 to January 2015. Total days of PN received prior to surgery, changes in weight and BMI, and changes to CRP and albumin in all patients receiving PN were analysed. Adverse events related to PN, including line-related complications, and post-operative complications were also recorded. Results: Of 62 operations performed for CD over the study period, 6 patients (4 male) received pre-operative PN. PN was administered via a PICC line with a dedicated lumen in all patients. All patients continued PO liquid intake and existing CD medications. 5 patients had stricturing and penetrating disease (3 with ileocaecal disease, and 2 with colonic disease). 2 of these patients had phlegmons, 2 had complex peri-anal fistulising disease, and 1 had a high output entero-cutaneous fistula. A further patient had isolated ileocolic stricturing disease. 4 patients required ileocaecal resection, 1 required panproctocolectomy and 1 sub-total colectomy. Pre-operative PN was administered for a mean of 41 days. Weight and BMI increased in all 6 patients (mean weight increased from 51.2 kg to 57.7 kg, mean BMI from 17.5 kg/m 2 to 19.8 kg/m 2 ). The weight gained was maintained at routine follow-up after surgery. Mean CRP improved from 35.5 to 18.3, and albumin from 35.5 g/L to 38.3 g/L. Mean post-operative stay was 12 days, and diversion stoma was not required in 80% (4 patients). Line complications (catheter related infection/thrombosis) were not seen. One patient (16.7%) required PN withdrawal 2 days before planned surgery for suspected line sepsis not confirmed on blood cultures. No serious post-operative complications occurred, and only a single patient required antibiotics post-operatively for a small collection (not requiring surgical or radiological intervention). Conclusion: In this small group of complex CD patients who received pre-operative PN, sustained weight gain and improvement in inflammatory markers was observed. Two recent studies suggest favourable postoperative outcomes, and our findings are in keeping with this. The role of optimisation with PN warrants further investigation and randomised controlled studies are required. Disclosure of interest: None Declared.